KLASIFIKASI ILMU DALAM ISLAM PERSPEKTIF IMAM AL GHOZALI - Muhammad Nur Hadi; Nurul Laylia; Syaifullah Syaifullah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
The background of this research is how the classification of knowledge according to Imam al-Ghazali in the book of Ihya 'ulumuddin. With the aim to describe the classification of science and the reasons of Imam al-Ghazali in the classification of knowledge contained in the book of Ihya' Ulumuddin. The benefits of this research are that parents today still pay attention to education for their children by not looking at the side between primary and secondary sciences. This study includes the type of literature that takes data from inanimate objects in the form of books or books, using a qualitative approach. using Content Analysis techniques in analyzing data based on the content contained therein. From the results of the study showed that Imam al-Ghazali classified science into two types namely fardlu 'ain and fardlu kifayah. Which is fardlu 'ain science only consists of syar'iyyah science and fardlu kifayah science consists of two kinds namely syar'iyyah science and ghoiru syar'iyyah science. Included in the primary sciences are religious sciences such as kalam science, tasawwuf science, and syariah science. Whereas secondary science is a branch of primary science such as mathematics, social sciences, natural sciences, health sciences and political sciences.